COVID toes: where do we stand with the current evidence? (2020)
Background: Numerous of cases of chilblains have been observed, mainly in young subjects with no or mild symptoms compatible with COVID-19. The pathophysiology of these lesions is still widely debated and an association with SARS-CoV-2 infection remains unconfirmed. Objectives: This paper focus on the unresolved issues about these COVID toes and in particular whether or not they are associated with COVID-19. Arguments: - The temporal link between the outbreak of chilblains and the COVID-19 pandemic is a first suggests a link between the two events. Journal Pre-proof 3 - Positive anti-SARS-CoV/SARS-CoV-2 immunostaining on skin biopsy of chilblains seem to confirm the presence of the virus in the lesions, but lack specificity and must be interpreted with caution. - Conversely, RT-PCR and anti-SARS-CoV-2 serology were negative in the majority of patients with chilblains. Therefore, SARS-CoV-2 infection can be excluded, with relative certainty, even after accounting for possible lower immunization in mild/asymptomatic patients and for some differences in sensitivity/specificity between the tests used. - Some authors hypothesize that chilblains could be the cutaneous expression of a strong type I interferon (IFN-I) response. High production of IFN-I is suggested to be associated with early viral control and may suppress antibody response. However, the absence of other cutaneous or extracutaneous symptoms as observed in other interferonopathies raises unanswered questions. - To date, a direct link between chilblains and COVID-19 still seems impossible to confirm. A more indirect association due to lifestyle changes induced by lockdown is a possible explanation. Improvement of chilblains when protective measures were adopted and after lifting of lockdown, support this hypothesis. Conclusion: Conflicting current evidence highlights the need for systematic and repeated testing of larger numbers of patients and the need for valid follow-up data that take into consideration epidemic curves and evolution of lockdown measures.